Technology Integration Models into adult education: TPACK and SAMR - Campos Retana, Roy Alberto (2021)
Global trends and COVID-19 have put the world into an educational challenge, boosting digital transformation. Although research studies had analyzed enablement’s and constraints of technology integration through virtual and face-to-face contexts, their focus has been on K-12, high schools, and higher education, but not on adult education. Through an analysis of available theory, this scientific essay develops a moderate approach that fills the gap between technology integration and executive education. This theoretical paper suggests that cognizance of TPACK and SAMR –tech frameworks– encourage instructors to reflect and reframe their mental schemes and integrate technology into their teaching practice. This work also sustains that such integration requires a dedicated process beyond the mere addition of technologies in the educational environment.